New genomic regions associated with white mold resistance in dry bean using a MAGIC population. Issue 1 (2nd February 2022) - Escobar, Edgar; Oladzad, Atena; Simons, Kristin; Miklas, Phillip; Lee, Rian K.; Schroder, Stephan; Bandillo, Nonoy; Wunsch, Michael; McClean, Phillip E.; Osorno, Juan M.
Abstract: Dry bean ( Phaseolus vulgaris L.) production in many regions is threatened by white mold (WM) [ Sclerotinia sclerotiorum (Lib.) de Bary]. Seed yield losses can be up to 100% under conditions favorable for the pathogen. The low heritability, polygenic inheritance, and cumbersome screening protocols make it difficult to breed for improved genetic resistance. Some progress in understanding genetic resistance and germplasm improvement has been accomplished, but cultivars with high levels of resistance are yet to be released. A WM multiparent advanced generation inter‐cross (MAGIC) population ( n = 1060) was developed to facilitate mapping and breeding efforts. A seedling straw test screening method provided a quick assay to phenotype the population for response to WM isolate 1980. Nineteen MAGIC lines were identified with improved resistance. For genome‐wide association studies (GWAS), the data was transformed into three phenotypic distributions—quantitative, polynomial, and binomial—and coupled with ∼52, 000 single‐nucleotide polymorphisms (SNPs). The three phenotypic distributions identified 30 significant genomic intervals [−log10 ( P value) ≥ 3.0]. However, across distributions, four new genomic regions as well as two regions previously reported were found to be associated with resistance. Cumulative R 2 values were 57% for binomial distribution using 13 genomic intervals, 41% for polynomial using eight intervals, and 40% for quantitative using 11 intervals. New resistant germplasm as well as new genomic regions associated with resistance are now available for further investigation. Core Ideas: A MAGIC population was developed to facilitate mapping and pyramiding of QTL related to white mold resistance. New genomic regions associated with white mold resistance are reported while some known regions are confirmed. Pinto and great northern beans with improved resistance to white mold were identified. Disease‐related candidate genes for white mold resistance were identified.